2014
DOI: 10.1007/978-3-319-07626-3_37
|View full text |Cite
|
Sign up to set email alerts
|

Management of Visual Clutter in Annotated 3D CAD Models: A Comparative Study

Abstract: Abstract. The use of annotations in CAD models has been an active area of research because of their ability to connect design information to specific aspects of the model's geometry. The effectiveness of annotations is determined by the ability to clearly communicate information. However, annotations can quickly create clutter and confusion as they increase both in number and complexity. Consequently, efficient interaction and visualization mechanisms become crucial. Despite recent standardizations of procedur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
3
3
1

Relationship

2
5

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 28 publications
0
6
0
Order By: Relevance
“…Alternatively, our study shows better acceptance of the unstructured nature of our approach as long as filtering and searching mechanisms are available. In our experiment, we showed that users that interact with 3D models with no visualization or filtering tools perform significantly worse than users with access to annotation management mechanisms, such as the proposed annotation manager [57]. …”
Section: Fig 6 Interface Of Annotation Manager Prototypementioning
confidence: 84%
See 1 more Smart Citation
“…Alternatively, our study shows better acceptance of the unstructured nature of our approach as long as filtering and searching mechanisms are available. In our experiment, we showed that users that interact with 3D models with no visualization or filtering tools perform significantly worse than users with access to annotation management mechanisms, such as the proposed annotation manager [57]. …”
Section: Fig 6 Interface Of Annotation Manager Prototypementioning
confidence: 84%
“…In one of our recent studies [57], we exposed the problem of visual clutter and the limitations of current annotation mechanisms to deal with this problem. Because the creation and management of annotation planes and the distribution of annotations among these planes are ultimately the user's responsibility, many designers often choose not to benefit from annotation tools because of the additional effort involved in this task.…”
Section: Fig 6 Interface Of Annotation Manager Prototypementioning
confidence: 99%
“…A custom plug-in was developed using Visual Basic .NET. The plug-in interface was designed as an additional tab in the SolidWorks main interface panel, as described in our previous work [14]. Model annotations are displayed in tabular form.…”
Section: Methodsmentioning
confidence: 99%
“…These annotations can be used to document the modeling process in a similar way to source code comments in a computer program. The additional layer of information provided by the annotations facilitates the understanding and reusability of the model [14]. Furthermore, when properly and sufficiently annotated, comprehensive design documentation could be generated automatically from models and assemblies.…”
Section: Annotated Models For Trainingmentioning
confidence: 99%
“…Such visual cues, which can come from automated analysis or manual mark-up processes, are known to make data understanding easier for the viewer [VETL18]. Finding relevant annotations, and presenting them in a comprehensible way without cluttering the display, however, is very challenging [CCJ14].…”
Section: Introductionmentioning
confidence: 99%